INFLUENCE OF PRE PRIMARY EDUCATION ON EMOTIONAL SKILL ACQUISITION OF PUPILS IN ILORIN SOUTH LOCAL GOVERNMENT AREA OF KWARA STATE - Hafees Tosin Sulyman; Alawaye Rukayat Damilola (CV. RADJA PUBLIKA, 2024)
The study examines the influence of pre-primary education on emotional skill acquisition of pupils in Ilorin south local government area of Kwara state. Descriptive survey research design was used. Three hundred and eighty-one (368) pupils were randomly selected for this study from twenty (20) schools both private and public using simple random sampling technique. Rating scale was used as the research instrument to measure the level of emotional skill acquisition of pupils. One research question and three hypotheses was formulated at 0.05 level of significance. The findings revealed the level of emotional skills acquisition of pupils’ in Ilorin South Local Government Area of Kwara State Mean (2.53) which indicate that the level of emotional skill acquisition of pupils’ in Ilorin South Local Government Area of Kwara State is high. Also, Preprimary education have significant influence on pupils’ emotional skill acquisition in Ilorin South Local Government Area of Kwara State (F 1.368)=.149, P<0.05). Also there was significant difference in emotional skills acquisition of pupils’ based on Gender (t =,783; df =366; P <0.05), this implies that male emotional skill acquisition (Mean= 38.03) is significantly higher than of female (Mean= 37.87). the findings also shows that there was significant difference in emotional skills acquisition of pupils’ based on school type (t = -,294; df = 366; P < 0.05). The researcher therefore recommends that every child should be exposed to preprimary school education and there should be more focus on pupils emotional.